Repeat-mediated recombination results in Complex DNA structure of the mitochondrial genome of Trachelospermum jasminoides - Yisha Cai; Haimei Chen; Yang Ni; Jingling Li; Jinghong Zhang; Chang Liu (BMC Plant Biology)
Abstract Background Trachelospermum jasminoides has medicinal and ornamental value and is widely distributed in China. Although the chloroplast genome has been documented, the mitochondrial genome has not yet been studied. Results The mitochondrial genome of T. jasminoides was assembled and functionally annotated using Illumina and nanopore reads. The mitochondrial genome comprises a master circular molecular structure of 605,764 bp and encodes 65 genes: 39 protein-coding genes, 23 transfer RNA (tRNA) genes and 3 ribosomal RNA genes. In addition to the single circular conformation, we found many alternative conformations of the T. jasminoides mitochondrial genome mediated by 42 repetitive sequences. Six repetitive sequences (DRS01–DRS06) were supported by nanopore long reads, polymerase chain reaction (PCR) amplifications, and Sanger sequencing of the PCR products. Eleven homologous fragments were identified by comparing the mitochondrial and chloroplast genome sequences, including three complete tRNA genes. Moreover, 531 edited RNA sites were identified in the protein-coding sequences based on RNA sequencing data, with nad4 having the highest number of sites (54). Conclusion To our knowledge, this is the first description of the mitochondrial genome of T. jasminoides. Our results demonstrate the existence of multiple conformations. These findings lay a foundation for understanding the genetics and evolutionary dynamics of Apocynaceae.